2020
DOI: 10.1515/nanoph-2020-0457
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale confinement of energy deposition in glass by double ultrafast Bessel pulses

Abstract: Ultrafast laser pulses spatially shaped as Bessel beams in dielectrics create high aspect ratio plasma channels whose relaxation can lead to the formation of nanochannels. We report a strong enhancement of the nanochannel drilling efficiency with illumination by double pulses separated by a delay between 10 and 500 ps. This enables the formation of nanochannels with diameters down to 100 nm. Experimental absorption measurements demonstrate that the increase of drilling efficiency is due to an increase of the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The evacuation of a fraction of the hot material via the void channel produced at the center of the Bessel beam, allows for quenching the relaxation and maintains the void structure even for parameters where the void would be partially or totally reclosed by the molten material around it. Recent results on double pulse illumination let us anticipate that double pulse could partially reduce the amount of the molten layer, and increase the temperature contrast between the optical axis and the surrounding lobes [35].…”
Section: Discussionmentioning
confidence: 99%
“…The evacuation of a fraction of the hot material via the void channel produced at the center of the Bessel beam, allows for quenching the relaxation and maintains the void structure even for parameters where the void would be partially or totally reclosed by the molten material around it. Recent results on double pulse illumination let us anticipate that double pulse could partially reduce the amount of the molten layer, and increase the temperature contrast between the optical axis and the surrounding lobes [35].…”
Section: Discussionmentioning
confidence: 99%
“…We attribute this effect to the impossibility for the ablated matter to be evacuated out of the hole in this regime of confined bulk ablation. [42,43] Increasing the energy should yield a larger volume of ablated matter, but which is further redeposited on the walls of the hole, thus strongly limiting the increase of the obtained hole diameter. Therefore, we cannot expect a direct correspondence between the local fluence profile and the hole diameter so that fitting the data for the hole diameter d with a threshold-based method would not be physically meaningful.…”
Section: Threshold-based Analysismentioning
confidence: 99%
“…[34] The pressure and temperature on the tube increase sharply, potentially up to the warm dense matter regime. [38,41] This leads to radial forces toward the tube center and outward, as in the case of surface excitation by an optical vortex. [42] In our case, a long column of material is pressurized, and the relaxation involves material transfer from bulk across the surface.…”
Section: Formation Mechanism Of the Nano-pillarsmentioning
confidence: 99%
“…A proof-of-principle has already been obtained in glass by Xie et al, with a single pulse shaped as a higher-order Bessel beam with circular polarization to generate a high-refractive index rod inside the bulk of glass. [37] Recent results have shown that zeroth-order Bessel beams induce, in a single shot, a very high energy density plasma, [38] thanks to the process of resonance absorption, [39] which occurs for polarization oriented perpendicular to the nano-plasma rod. With the aim of generating extreme states of matter, we have used a radially-polarized first-order Bessel beam, with a focal region shaped as a high-aspect ratio cylinder with an 800 nm diameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation